Technical Assessment Of Mud Handling Planning With Dredger Pump In Mining Front Area Of Pt. Makmur Lestari Primatama, Southeast Sulawesi, Indonesia - Reza Aryanto; Herza Mitha Fortuna; Purwiyono, Taat Tri; Suliestyah, Suliestyah (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The high intensity of rain can affect mining activities because rainwater will be collected and stored in the area with the lowest elevation. In mining areas that have the lowest elevation point, namely the pit area, this will have an impact on mining activities. The pit area will not be disturbed if water or eroded slopes will enter and be accommodated in well-made drainage and vice versa if drainage is not formed properly, water and mud will be retained and accommodated in the pit area. If the water and mud are left unchecked, the water will overflow and mining will be temporarily halted, affecting the previously planned mining system. In this case, the pit whose water has been pumped out leaves the mud at the bottom of the pit trapped, so action is needed to remove the mud from the pit area and the need for qualified tools according to the existing mud criteria. The mud at PT Makmur Lestari Primatama has an SG criteria of 1.39 (top elevation mud) - 1.5 (bottom elevation mud) with mud grains of 0.005mm to 2mm, it can be concluded that the mud has liquid mud criteria to hard mud. So that the determination of a tool to be able to move mud using a pump, the selection of this pump There are three important parameters: Grain size, Specific Gravity, and also variations in material concentration that must be considered because they can affect the total head or flowrate. The difference between the Slurry pump and the dredger pump is in the pumping process, the dredger pump is able to pump hard mud with the help of a little water while the slurry pump is difficult to pump hard mud because it requires quite a lot of water to pump it. Therefore, a dredger pump is chosen to move the mud in the mining area so that it can pump liquid mud to hard mud, the selection of this dredger pump is based on pump specifications including max capacity 120-200m3/h, solid handling 35mm - 60mm, speed 1180 RPM, and effieciency 46%-51%. The planning analysis of the use of dredger pumps uses the Bernoulli equation and the amount of mud that must be pumped using the USLE method. Based on the results of a series of studies that have been carried out, researchers found that the total potential erosion is 8,574.2 tons/year, the total actual erosion is 7,716.8 tons/year, and the total volume of mud that must be pumped is 5,074.86m3 with a slurry weight of 1,448.2 kg/m3. So the most ideal dredger pump for this purpose is Dragflow HY85A with a capacity of 210m3/h, pumping hours of 16.6 hours / day, pumping duration of 2 days 15 hours and efficiency of 40% using HDPE type 10 inch diameter pipe.